The influence of nickel layer thickness on microhardness and hydrogen sorption rate of commercially pure titanium alloy - Kudiyarov V. N. Victor Nikolaevich; Kashkarov E. B. Egor Borisovich; Syrtanov M. S. Maksim Sergeevich; Yugova I. S. (2016, 2016)
Title screen